Tetracycline Regulator Expression Alters the Transcriptional Program of Mammalian Cells - Hackl, Hubert; Rommer, Anna; Konrad, Torsten A.; Nassimbeni, Christine; Wieser, Rotraud (PLOS ONE, 2010)
Background Tetracycline regulated ectopic gene expression is a widely used tool to study gene function. However, the tetracycline regulator (tetR) itself has been reported to cause certain phenotypic changes in mammalian cells. We, therefore, asked whether human myeloid U937 cells expressing the tetR in an autoregulated manner would exhibit alterations in gene expression upon removal of tetracycline. Methodology/Principal Findings Microarray analyses revealed that 172 and 774 unique genes were significantly differentially expressed by at least 2- or 1.5-fold, respectively, when tetR expressing U937 cells were maintained in media with or without the antibiotic. Conclusions/Significance These alterations in gene expression are likely to contribute to the phenotypic consequences of tetR expression. In addition, they need to be taken into consideration when using the tetR system for the identification of target genes of transcription factors or other genes of interest.